Hubungan Lingkungan Kerja terhadap Kinerja Organisasi pada Perawat di Rumah Sakit Dirgahayu Kota Samarinda - Cantika, Arti Wulan; Prastika, Netty Dyan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
A hospital must be able to maintain the work environment to increase worker productivity, which will then affect the achievement of maximum hospital performance. This study aims to determine the relationship between work environment and organizational performance. The method used in this research is the quantitative method. The participants in this study were 75 nurses who worked at Dirgahayu Hospital, Samarinda City. Sampling using a simple random sampling technique. The data analysis technique used was correlation. Data were analyzed with the help of the SPSS version 27.0 for Windows program. Based on the results of the research that has been done, there is a linear and positive influence between the variables of organizational performance and the work environment.